A high resolution SEM study of the effects supplementation different ratio of n-6:n-3 on the endometrial pregnant rat - Kassem, Amira; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Mohamed Mustapha, Noordin (Macrothink Institute, 2017)
This study, therefore, aims to investigate the effects of dietary fatty acids onendometrial pinopode expression. Twenty eight rats were randomly divided into four groups (seven rat per treatment). Treatment diets were rat chow only control diet ( con ), rat chow containing 0.9 ml soybean oil (SO) + 0.9 ml cod liver oil (CLO) the ratio 1:1, rat chow added with 1.5 ml SO + 0 .3 ml CLO the ratio 6:1 and rat chow added with 1.74 ml SO + 0.06 ml CLO the ratio 30:1 ,feeds of 15g/ day were given and water was available ad libitum .The endometrial samples were evaluated under SEM. developing pinopodes were seen during increasing progesterone concentrations especially in Diet 1:1 group, and regressing pinopodes were found with decreasing progesterone in Diet 30:1 groups. In both Diet 1:1 treated and control animals, on days 15 of pregnancy, scanning electron micros copy revealed the microvilli of the uterine epithelial cells in the treated animals were more dense than those in the Diet 30:1 treated animals.